A STUDY OF USING POP SONGS TO PROMOTE NEW VOCABULARY LEARNING FOR SECONDARY SCHOOL STUDENTS - Borisai, Thippawan; Dennis, Nutprapha K. (International Journal of Research -GRANTHAALAYAH, 2016)
The purpose of this study aimed to1) promote students’ ability in learning new vocabulary through pop songs and 2) to investigate students’ opinions toward using pop songs in learning new vocabulary of grade 10 students at YangchumnoiPittayakom school, in Yangchumnoi district of Sisaket province. The sample who participated in this study were 40 grade 10 students at YangchumnoiPittayakom school derived by purposive sampling technique. The instruments were pretest and posttest, lesson plans and a questionnaire which was used to find the student’s opinions towards using pop songs method. The data collection were analyzed with the mean, standard deviation and t-test. The research finding of the study showed that teaching through pop songs increased students’ vocabulary ability for foreign language learners with significant value at .01 level. The students had the positive opinions toward using pop songs methods. It also revealed that the pop song technique was an effective tool to promote students’ vocabulary ability, made students cheerfully participate in class and increased motivation in learning English.